Analisis Resiko Penipuan Dalam Pembelian Online Di Instagram (Perspektif Konsumen) - Ardi, Nizar Septa; sukaris, sukaris (Jurnal Mahasiswa Manajemen, 2023)
Background – In an era where it is easier to get access to communicate, exchange information, even to the buying and selling process, many online businesses have been running. Objective – The purpose of this study is to identify the causes of fraudulent online purchases on Instagram and the impact of this fraud. Design / Methodology / Approach – Researchers used a qualitative approach. The informants in this study were 7 informants. Data collection was carried out by interview. Test the validity of the data using source triangulation and membercheck. Findings – The results of the research that have been done show that the occurrence of cases of online fraud on Instagram is caused by a lack of caution from some informants and an element of intent from the seller. The impact after the occurrence of the online fraud case differed among several informants. Some informants will still make repeat purchases, but be careful, and do not repurchase on Instagram. Research Implication – It is hoped that it can research online purchase fraud cases more widely, not only researching fraud cases on Instagram but also researching fraud cases in other places such as other social media, and marketplaces. It is hoped that the next research can dig deeper into online fraud and not only from a consumer perspective with a wider scope. Limitations – Unable to conduct direct interviews with several informants due to the timing of the research during the Covid19 pandemic.